The Characterization of Active Compound of Pedada Magrove Plants (Sonneratia caseolaris) Which HaveThePotential as Natural Antioxidants - Latief, Madyawati (Journal of Chemical Natural Resources, 2019)
The present research aimedto isolate the compound from the acetone fractions of pedada leaves (Sonneratia caseolaris) and test its antioxidant activity. The extraction wasperformed usinga multi-stage maceration method. The separation and purification were done using a vacuum and gravitational column chromatography whereasthe antioxidant activity was tested with theDPPH method. The structural elucidation of the compound was performed by spectroscopy data of UV, IR, alsoone- and two-dimensional NMR. The appearance of the pure isolate was odorless yellow crystal. Based on the spectroscopy data, the compound wasstigmasta-5,22-dien-3-ol. The activity testing of the extract antioxidant and pure isolate with IC50showed a value of 166.2 ppm dan 134.4 ppm, respectively.